Ownership of consumer electronics is associated with measures of adiposity during health transition in Vanuatu. Issue 2 (15th October 2016) - Sun, Cheng; Pomer, Alysa; Dancause, Kelsey N.; Chan, Chim W.; Olszowy, Kathryn M.; Silverman, Harold; Lee, Gwang; Tarivonda, Len; Taleo, George; Regenvanu, Ralph; Kaneko, Akira; Weitz, Charles A.; et al.
Abstract: Objective: The Republic of Vanuatu, like many developing nations, is undergoing a rapid health transition. Our previous study identified several behavioral risk factors for the rising prevalence of obesity. Unexpectedly, daily time spent using television and radio was revealed as a protective factor for obesity in 2007. In this study, we sought to explore associations between ownership of consumer electronics (CE) and measures of adiposity in Vanuatu in 2011. Methods: We surveyed 873 adults from five islands varying in level of economic development. Height, weight, and waist circumferences; triceps, subscapular, and suprailiac skinfolds; and percent body fat by bioelectrical impedance were measured. Ownership of eight types of CE, diet through 24‐h dietary recall and leisure‐time activity patterns were assessed using a questionnaire. Results: Participants from more developed islands owned more types of CE, and revealed higher measures of adiposity on average as well as higher prevalence of obesity/central obesity. When controlling for demographic factors, and dietary and activity patterns, increased measures of adiposity and risk for obesity/central obesity were associated with ownership of cellphones, music players, televisions, video players, microwaves, and/or refrigerators. Positive correlations between CE ownership and measures of adiposity were mainly observed among men on the two most developed islands. Conclusions: The results of this study indicate a possible role of CE use in the rising prevalence of obesity and the shift to a sedentary lifestyle in Vanuatu and many other modernizing regions, where prevention efforts including education on healthy use of CE are imperative.